2022
DOI: 10.3389/fmolb.2021.748360
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiles of Age-Related Osteoarthritis Uncover Underlying Heterogeneity Associated With Disease Progression

Abstract: Objective: Osteoarthritis (OA) is the most common chronic degenerative joint disease, which represents the leading cause of age-related disability. Here, this study aimed to depict the intercellular heterogeneity of OA synovial tissues.Methods: Single-cell RNA sequencing (scRNA-seq) data were preprocessed and quality controlled by the Seurat package. Cell cluster was presented and cell types were annotated based on the mRNA expression of corresponding marker genes by the SingleR package. Cell-cell communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our in vitro findings suggested that this pro-inflammatory environment was caused by an imbalance in the activation of pro-inflammatory and pro-regenerative immune cells, resulting in fibrosis and the onset and progression of OA. This is in line with previous literature where an imbalance in the infiltration and residence of pro-inflammatory cells are seen in the synovial joint during OA initiation and progression ( 12 14 ). To test this in vivo, an immunomodulatory cell-based treatment was developed with the goal of mimicking and promoting the crucial events observed during functional tissue regeneration.…”
Section: Resultssupporting
confidence: 93%
“…Our in vitro findings suggested that this pro-inflammatory environment was caused by an imbalance in the activation of pro-inflammatory and pro-regenerative immune cells, resulting in fibrosis and the onset and progression of OA. This is in line with previous literature where an imbalance in the infiltration and residence of pro-inflammatory cells are seen in the synovial joint during OA initiation and progression ( 12 14 ). To test this in vivo, an immunomodulatory cell-based treatment was developed with the goal of mimicking and promoting the crucial events observed during functional tissue regeneration.…”
Section: Resultssupporting
confidence: 93%
“…Especially stem cells are often differentiated into joint tissue-specific cells and progenitor cells ( Lin et al, 2014 ; O’Grady et al, 2019 ; Pirosa et al, 2021 ) for bone, cartilage, adipose, or connective tissue cells using differential cultivation protocols ( Lin et al, 2019 ). Given the cell population heterogeneity of resident mature and progenitor cell types in native OA tissues ( Stephenson et al, 2018 ; Cheng et al, 2021 ; Wang et al, 2021 ; Liu et al, 2022 ), stem cell approaches for future in vitro models must provide tissue-specific mature cell types with high phenotypic and genotypic authenticity in addition to a variety of heterogeneous progenitor cells. The direct and indirect crosstalk between various progenitor and adult cell subpopulations will in turn further advance the authenticity as well as the inflammatory responsiveness of the next-generation microsystems.…”
Section: Bioengineering Roadmap—requirements For the Next Generation ...mentioning
confidence: 99%
“…As a final remark for this bioengineering road ahead, the necessity of artificial intelligence and deep learning ( Hashemzadeh et al, 2021 ) to support faster data analysis and interpretation arise, since throughput and content as both throughput and content of our bioengineered systems will also potentiate the number of individual analysis parameters (e.g., secretion profile, mRNA expression, structural imaging, multidimensional cell morphologies, and interactions, etc.). Multi-parametric datasets can further benefit from potent high-content analysis schemes such as single-cell sequencing ( Liu et al, 2022 ) and advanced mass spectrometry imaging ( Rossiter et al, 2021 ; Vandenbosch et al, 2021 ). Finally, validation of microphysiological disease models must ideally be benchmarked against human data; however, no human patient data are available for the early stages of arthritic disorders.…”
Section: Bioengineering Roadmap—requirements For the Next Generation ...mentioning
confidence: 99%
“…Immune cells, such as macrophages and T cells, associated effector cytokines, and cytokine receptors expressed by synoviocytes are involved in the development of OA. 30 Macrophages, the most abundant type of immune cells, produce inflammatory cytokines, including TNF, IL-1β, IL-18, TGF-β1, and IL-8. 30 Chou et al 26 found a novel IR-MΦ population with high expression of immunoregulatory genes that might play roles in clearing cell remnants and degraded tissues and in modulating immune responses in the synovium (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“… 30 Macrophages, the most abundant type of immune cells, produce inflammatory cytokines, including TNF, IL-1β, IL-18, TGF-β1, and IL-8. 30 Chou et al 26 found a novel IR-MΦ population with high expression of immunoregulatory genes that might play roles in clearing cell remnants and degraded tissues and in modulating immune responses in the synovium (Table 2 ). Sebastian et al 31 identified resident Lyve1 hi Folr2 hi macrophages and Trem2 hi Fcrls + recruited macrophages that acted as chondroprotectors and aided in joint injury healing.…”
Section: Introductionmentioning
confidence: 99%